Loyalty myths : (John Wiley & Sons, 2005)
In Loyalty Myths, the authors have assembled 53 of the most common beliefs about customer loyalty – all of them wrong or misconceived! Each of the beliefs in this book is debunked with real-world examples. While other books speak in platitudes; this book is the only one to validate each proposition with real data.